Comparison of Dobutamine and Treadmill Exercise Echocardiography in Detecting and Predicting the Extent of Coronary Artery Disease (University Heart Journal, 2025)
Background: Coronary artery disease (CAD) continues to be a major cause of morbidity and mortality worldwide. Timely and precise detection is essential for appropriate intervention and management. Two commonly used non-invasive diagnostic techniques for detecting coronary artery disease are dobutamine stress echocardiography and treadmill exercise echocardiography. This study aimed to compare the effectiveness of dobutamine and treadmill exercise echocardiography for detecting coronary artery disease. Methods: This prospective observational study was conducted at the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2000 to December 2021. As study subjects, a total of 77 suspected patients of coronary artery disease were enrolled by using a purposive sampling technique. For data analysis MS Office tools and SPSS Version 23.0 were used. Results: In comparing the peak hemodynamic data during dobutamine echocardiography and treadmill exercise electrocardiography, we found statistically significant differences (p